Aplicação da Micromorfologia de Solos ao Estudo de Sedimentos Alúvio-Coluviais em Cabeceiras de Vale - SILVA FERREIRA, GLAUCIA MARIA DOS SANTOS; TEIXEIRA DE OLIVEIRA, MARCELO ACCIOLY (Pesquisas em Geociências, 2006)
<!-- .p { text-align: justify; } --> Previous work on the role played by valley head areas in humid regions brought to light geomorphological units of the drainage net in which erosion and sedimentation would tend to be recurrent in time and space. Valley heads studied in Brazil had already proved to be very sensible to gully erosion processes, which, besides its importance to land degradation, also is a common process of hillslope evolution on humid regions. Gully erosion carries out from slopes important amounts of sediments, which may either, accumulate as proximal colluvium and alluvium or be conveyed through the drainage net. When colluvium and alluvium accumulate in proximal areas sedimentary structures may be preserved allowing the study of evolutionary processes. This paper is an attempt to apply micromorphological analysis to the study of the sedimentary structures preserved in gullied hillslopes of some southern Brazilian areas. The deposits are dated either in accordance to the supposed age of the gully incision, as estimated by aerial photographs, or by the record, in the field, of the depositional event. As a result, the age of the study deposits ranges from about 200 to 30 years, including fresh sediments just deposited one day before sampling. The paper stresses the relationship between macroscopic structures and micromorphological parametrical description, emphasizing interpretation of sedimentary structures as the result of variable overland flow rates on the gullied hillslopes.